2007
DOI: 10.5860/crl.68.5.405
|View full text |Cite
|
Sign up to set email alerts
|

Retaining and Advancing Librarians of Color

Abstract: This paper will explore the concept of group mentoring and the possible impact of creating learning communities on retention. It will consider one model, a training institute held biennially at the University of Minnesota, which is directed to early-career librarians of color, and will explore the impact of this institute, which includes group mentoring, on retention and professional contributions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 9 publications
(6 reference statements)
0
9
0
Order By: Relevance
“…Mentoring is traditionally defined as a dyadic relationship where a senior member (mentor) guides a junior member (mentee) through a series of transitional stages-through both formal and informal interactions-to help expand professional development and help guard against the negative effects of psychosocial influences on wellness (Davidson & Foster-Johnson, 2001;de Janasz & Sullivan, 2004;P. Johnson, 2007;Torrens et al, 2017).…”
Section: Validating Mentorshipmentioning
confidence: 99%
“…Mentoring is traditionally defined as a dyadic relationship where a senior member (mentor) guides a junior member (mentee) through a series of transitional stages-through both formal and informal interactions-to help expand professional development and help guard against the negative effects of psychosocial influences on wellness (Davidson & Foster-Johnson, 2001;de Janasz & Sullivan, 2004;P. Johnson, 2007;Torrens et al, 2017).…”
Section: Validating Mentorshipmentioning
confidence: 99%
“…It serves as an example of how group mentoring, networking, and professional development can function as ways to ensure successful retention. 8 Another program held at Colorado State University, "The New Beginnings Program," brings senior library faculty of color together with junior library faculty of color to help socialize them into the academic workplace. 9 This program offers junior faculty the opportunity to seek out research advice, develop grant-writing skills, and gain a better understanding of the faculty evaluation process.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mentoring has benefits for minorities, as well as for the majority of academic librarians, and the research offers insights into how these benefits from mentoring can positively affect retention rates of minority librarians (Bonnette, 2004;Johnson, 2007;and Olivas & Ma, 2009). Bonnette (2004) provides statistical data taken from both the 1990 and 2000 United States census to illuminate how our minority population is increasing exponentially and suggests that half of the population of the United States will be ethnic minorities by the year 2050.…”
Section: Benefits Of Mentoring Minoritiesmentioning
confidence: 99%
“…Research was conducted by Johnson (2007) at the University of Minnesota in the Institute for Early Career Librarians from Groups Underrepresented in the Profession to determine the influence of group mentoring on retention for librarians of color. The research indicated that librarians of color often feel isolated, intimidated, and alienated due to joining a predominantly white profession where others may be older and have more job-related experience.…”
Section: Benefits Of Mentoring Minoritiesmentioning
confidence: 99%